Prelinguistic Relational Concepts: Investigating Analogical Processing in Infants. Issue 5 (20th May 2015) - Ferry, Alissa L.; Hespos, Susan J.; Gentner, Dedre
<x xml:space="preserve">Abstract</x> This research asks whether analogical processing ability is present in human infants, using the simplest and most basic relation—the same–different relation. Experiment 1 (N = 26) tested whether 7‐ and 9‐month‐olds spontaneously detect and generalize these relations from a single example, as previous research has suggested. The attempted replication failed. Experiment 2 asked whether infants could abstract the relation via analogical processing (Experiment 2, N = 64). Indeed, with four exemplars, 7‐ and 9‐month‐olds could abstract the same–different relation and generalize it to novel pairs. Furthermore, prior experience with the objects disrupted learning. Facilitation from multiple exemplars and disruption by individual object salience are signatures of analogical learning. These results indicate that analogical ability is present by 7 months.